Data Processing System for NonStationary Processes Based on The Synthesis of Soft Computing Components - Kholmonov Sunatillo Makhmudovich; Mirsanova Gulbahor Muhammadi qizi (Genius Journals, 2022)
The problem has been formulated and the scientific and methodological foundations of data processing systems for non-stationary objects based on neural networks, fuzzy set models, fuzzy inference algorithms, and neuro-fuzzy networks have been developed. Are proposed mechanisms for structural and parametric identification, finding a set of terms of linguistic variables, rules of inference, determining the coefficients of fuzzy rules, using the properties of self-adaptation, self-regulation, network organization, and the formation of databases and knowledge. The efficiency of the implemented algorithms was evaluated on the basis of test unimodal and multimodal output functions.
Keywords: Non-Stationary Process; Processing, Neural Network; Fuzzy Set; Fuzzy Inference